1990
DOI: 10.1103/physrevlett.65.2370
|View full text |Cite
|
Sign up to set email alerts
|

Defects in roll-hexagon competition

Abstract: The defects of a system where hexagons and rolls are both stable solutions are considered. On the basis of topological arguments we show that the unstable phase is present in the core of the defects. This means that a roll is present in the penta-hepta defect of hexagons and that a hexagon is found in the core of a grain boundary connecting rolls with different orientations. These results are verified in an experiment of thermal convection under non-Boussinesq conditions. PACS numbers: 47.20. Bp, 47.25.Qv D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
75
0

Year Published

1991
1991
2013
2013

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 152 publications
(79 citation statements)
references
References 11 publications
4
75
0
Order By: Relevance
“…10). in an analysis of amplitUde equations, Ciliberto et al 42 showed that a grain boundary between two oblique rolls (stripes) gives rise locally to hexagons, and that, in the defect of hexagons, a roll (stripe) is present. We conjecture that in a parameter region where stripes and hexagons are nearly equally sta-.…”
Section: Nariomentioning
confidence: 99%
“…10). in an analysis of amplitUde equations, Ciliberto et al 42 showed that a grain boundary between two oblique rolls (stripes) gives rise locally to hexagons, and that, in the defect of hexagons, a roll (stripe) is present. We conjecture that in a parameter region where stripes and hexagons are nearly equally sta-.…”
Section: Nariomentioning
confidence: 99%
“…20 Many complex patterns exhibit striking, isolated objects like point defects, e.g., dislocations, 21,22 disclinations, 23 or penta-hepta defects. 24,25 Dislocations often take on the form of spirals, as is the case for points of vanishing oscillation amplitude in spatially extended oscillations. 26,27 Similar spirals also arise in excitable systems.…”
Section: Introductionmentioning
confidence: 99%
“…Equations of motion (4) indicate that the penta-hepta defect is driven by superposition of two Peach-K ohler forces corresponding to a strain at singular modes 2,3. If K 2;3 = 0, defect does not move.…”
mentioning
confidence: 99%